2021
DOI: 10.3390/su132011374
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Factors Affecting Food Loss and Waste and Sustainable Mitigation Strategies: A Logistics Service Providers’ Perspective

Abstract: This study investigates the causes of food loss and waste (FLW) from the perspective of logistics service providers (LSPs) and provides sustainable options for the Chinese market. To this end, this study reviews the literature on FLW and cold chain logistics published from 2008–2021. Until recently, little attention has been paid to understanding FLW drivers from the LSP perspective. This critical systematic literature review (SLR) aims to identify the potential drivers of FLW and provide a coherent and integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 61 publications
0
12
1
Order By: Relevance
“…The warehouse operator is expected to provide refrigerated warehouses, to store temperature-sensitive products at specified temperatures while the transporters or carriers are responsible for physically transhipment of temperature-sensitive products from the supply origin to the desired destinations, including distribution centres, retailers, and end consumers. The logistics service providers also play a critical role in ensuring the safe and efficient transportation, storage, and handling of temperature-sensitive products throughout the cold value chain [5][6][7], [60], [63][64][65][66].…”
Section: Cold Chain Logistics Service Providers Categories Cold Chain...mentioning
confidence: 99%
See 3 more Smart Citations
“…The warehouse operator is expected to provide refrigerated warehouses, to store temperature-sensitive products at specified temperatures while the transporters or carriers are responsible for physically transhipment of temperature-sensitive products from the supply origin to the desired destinations, including distribution centres, retailers, and end consumers. The logistics service providers also play a critical role in ensuring the safe and efficient transportation, storage, and handling of temperature-sensitive products throughout the cold value chain [5][6][7], [60], [63][64][65][66].…”
Section: Cold Chain Logistics Service Providers Categories Cold Chain...mentioning
confidence: 99%
“…A study by [70] suggests that improving the cold-chain logistics system through use of intelligent methods. Furthermore, the studies of [71], [24], [72], [7], [73], and [74]. examined the challenges of logistics service providers in providing effective services to consumers and suggested that meeting regulatory requirements, demands, proactive compliance strategies, continuous training programs, and having effective communication with service stakeholders will alleviate these challenges.…”
Section: Challenges Faced By Logistics Service Providers In Nigeriamentioning
confidence: 99%
See 2 more Smart Citations
“…Poor design of logistics networks can be a cause of FW (Balaji and Arshinder, 2016;de Moraes et al, 2020;Magalhães, Ferreira and Silva, 2021), since it can lead to hold-ups in logistics and SC aging, where products spend most of their shelf lives in the SC instead of in retails or consumers' homes (Göbel et al, 2015;Akkas, Gaur and Simchi-Levi, 2019;Turan and Ozturkoglu, 2021;Yan, Song and Lee, 2021). FW caused by logistics issues is increased by the lack of adequate infrastructures, such as refrigerated storage facilities and vehicles, or good roads, with this lack eventually leading to cold chain inefficiencies or interruptions (Bilska et al, 2016;Canali et al, 2017;Diaz-Ruiz et al, 2018;de Moraes et al, 2020;Magalhães, Ferreira and Silva, 2021).…”
Section: Causes Of Food Waste In the Supply Chainmentioning
confidence: 99%